The impact of the COVID-19 pandemic on undergraduate and postgraduate students: A cross-sectional survey - Zhu, Lu; Zhou, Ying; Huang, Yiyue; Lei, Xinxin; Guo, Haoran; Hu, Yibo; Wu, Songjiang; Lei, Li; Guo, Aiyuan (Frontiers in Psychiatry, 2023)
Background: The COVID-19 pandemic has impacted many facets of life. This study focuses on undergraduate and postgraduate students in China to explore how the pandemic has affected health status, daily life, learning situations, graduation-related situations, and their studies or work planning. Methods: This study sent online questionnaires to 2395 participants to investigate the extent to which they were affected by the epidemic in the various aspects mentioned above and to understand what help they tend to get in the face of these effects. Results: A total of 2000 valid questionnaires were collected. The physical health of 82.90% of the respondents was affected to varying degrees, with male students, non-medical students, and graduates being more affected than female students, students with medical majors, and non-graduates, respectively. The proportion of students affected by mental health, the total amount of physical exercise, emotional life, and interpersonal communication was 86.35%, 88.65%, 80.15%, and 90.15%, respectively. Compared with medical students and non-graduates, non-medical students and graduates were more affected. In addition, students' learning and graduation conditions have also been affected to a certain extent: 13.07% of students may not be able to graduate on time, and the proportion of postgraduate students’ graduations affected was higher than that of undergraduate students. Conclusions: The COVID-19 pandemic has affected the health status of students, their daily lives, learning situations, and so on to varying degrees. We need to pay attention to the issues, provide practical solutions and provide a basis for better responses to similar epidemics in the future.